2022
DOI: 10.18239/ocnos_2022.21.2.2839
|View full text |Cite
|
Sign up to set email alerts
|

Procesos cognitivos y ejecutivos asociados a la expresión escrita infantil

Abstract: Aprender a escribir es clave para transitar con éxito la Educación Primaria. En los grados escolares intermedios se registra un progreso significativo en la escritura infantil, debido al desarrollo lexical y cognitivo. En línea con este postulado, el objetivo del estudio fue analizar el valor predictivo de la atención, percepción, planificación, memoria de trabajo y memoria a largo plazo en tareas de expresión escrita en escolares argentinos. Participaron 168 niños y niñas, entre 8 y 11 años de edad, que cursa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In sum, Moreno's study [24] indicated that working memory, long-term memory retrieval and visuospatial skills contribute to children's low-level translating processes to achieve coherent and fluent sentence writing. In the following section, we will refer to a study that examined the role of these memory systems in children's higher-level writing skills, analyzing different text dimensions as the outcome of planning and reviewing processing.…”
Section: The Role Of Long-term Memory and Working Memory In Lower-lev...mentioning
confidence: 97%
See 3 more Smart Citations
“…In sum, Moreno's study [24] indicated that working memory, long-term memory retrieval and visuospatial skills contribute to children's low-level translating processes to achieve coherent and fluent sentence writing. In the following section, we will refer to a study that examined the role of these memory systems in children's higher-level writing skills, analyzing different text dimensions as the outcome of planning and reviewing processing.…”
Section: The Role Of Long-term Memory and Working Memory In Lower-lev...mentioning
confidence: 97%
“…Along with reading, writing is a distinctively human and highly complex skill of paramount importance for academic achievement (and daily life activities as well) [23,24].…”
Section: The Role Of Long-term and Working Memory In Children's Writi...mentioning
confidence: 99%
See 2 more Smart Citations
“…La elección de esta prueba fue debido a que no todas las variables de la distribución contaron con características de normalidad según el estadístico Kolmogorov-Smirnov (K-S). Al no contar con baremos locales de ambos instrumentos, se utilizó la distribución intra-muestral avalados por estudios previos en el ámbito local (Moreno, et al, 2022). Así se identificaron los niños y niñas con bajo, medio y alto rendimiento, siguiendo el criterio de las medidas de posición (percentiles y cuartiles).…”
Section: Analisis De Datosunclassified